I understand that we write T(x,y) as T(x,0)+T(0,y) and then we project operator T as such H+H\to H (x_{1},x_{2})\to x_{i} but then from T(x,0) we get that T(x,0)=projection_{1}T(x,0)+projection_{2}T(x,0) and since T(0)=0 we obtain that
T(x,0)=proj_{1}T(x,0)=T(x) if I understood correctly, that is we obtain operator A from the matrix A B C D, in a similar manner we proceed with T(0,y) and we get a mapping on T(y) which I believe would be a mapping D. but how do we obtain the b,c operators, sorry for asking a lot, want to understand this